The madden-julian oscillation modulates the air quality in the maritime continent - Kuwata, Mikinori (Amer Geophysical Union, 2021)
Air quality in the Maritime Continent, which worsens particularly during peatland fire periods, causes climate and environmental concerns. The occurrence of peatland fire haze has been related to the interannual variations of the El Nino-Southern Oscillation, Indian Ocean Dipole, and inter-seasonal monsoon cycle. However, the factors affecting the region's air quality on subseasonal timescales have not been clearly identified. We investigated the role of the Madden-Julian Oscillation (MJO), which has a 30-90-day cycle, in air quality using a long-term observation data set from Malaysia. The results show that in MJO Phase 3, during which the region is covered by convective clouds, only accounted for 4 +/- 2% of high PM10 concentration days (daily average PM10 concentration at site X > average + standard deviation of daily average PM10 concentration at site X) among all active MJO periods. In contrast, the corresponding values were considerably higher in MJO Phases 1 and 5-8. The MJO also modulated CO and ozone concentrations. This study shows that the MJO influences air quality during both fire and non-fire seasons, demonstrating that variations in wildfire activity are not the only cause of air quality changes. Other factors, such as precipitation, also need to be considered to better understand the relationship between the MJO and air quality.